Using modern technologies in the educational process of the college - D. K. Smolyakova (Вестник университета)
The results of a sociological study that allows us to evaluate the experience of using modern technologies by students in the educational process of the Sevastopol College of service and trade have been presented. Sevastopol College of service and trade adheres to the course of innovativeness and processability in its activities. Taking into account innovative approaches to graduate training, the Sevastopol College of service and trade development Program is being built as a tool for professional and personal formation and development of a highly qualified specialist, teachers have innovative initiatives, and students are ready to accept innovations. College of services and Commerce of Sevastopol has an unrealized potential for improving the system of using modern educational and educational technologies in the educational process. However, according to students, the main obstacles to the introduction of new educational technologies in the College are weak technical equipment of the learning process, insufficient training of teaching staff and a special conservative public awareness of the educational process. Studying the experience of students of the Sevastopol College of service and trade in combination with the use of modern educational technologies will help to identify promising areas in this area.